Collaboration for a living lab for people toward low-emission food system development in Kenya - Habermann, Birgit (CGIAR System Organization, 2022)
A living lab makes us think of a city or landscape as an open laboratory, a geographical space where scientists, policymakers, entrepreneurs, innovators, governance structures, and citizens can “plug in” to test and scale innovations, and new technologies, that still need to be made “field proof,” but in a real-life setting